Sigla lgbtqiapn+ e as dificuldades e preconceitos no mercado de trabalho - MIGUEL, Aparecida Donizeti; SANTOS, Bianca Amaral dos; TEODORO, Renan Noronha (060, 2025)
Organizações como a Aliança Nacional LGBTQIAPN+ e a Associação Brasileira de Lésbicas, Gays, Bissexuais, Travestis, Transexuais e Intersexuais (ABGLT) oferecem apoio e recursos para pessoas LGBTQIAPN+. * Existem diversas iniciativas e projetos que visam promover a inclusão de pessoas LGBTQIAPN+ no mercado de trabalho. A luta contra o preconceito é um esforço contínuo, e a conscientização e a ação são fundamentais para criar um mercado de trabalho mais justo e inclusivo para todos.

Organizations such as the National LGBTQIAPN+ Alliance and the Brazilian Association of Lesbians, Gays, Bisexuals, Transvestites, Transsexuals and Intersexuals (ABGLT) offer support and resources for LGBTQIAPN+ people. * There are many initiatives and projects that promote the inclusion of LGBTQIAPN+ people in the job market. The fight against prejudice is an ongoing effort, and awareness and action are key to creating a fairer and more inclusive job market for everyone.
The acronym lgbtqiapn+ and the difficulties and prejudices in the job market
Keywords: Recursos humanos; Gestão e Negócios